Efektivitas Pendekatan PMRI Terhadap Hasil Belajar Siswa Kelas IV Materi Pecahan Senilai di Mis Setia Bhakti Trawas - Agustyarini, Yhasinta; Masruroh, Hanik (Chalim Journal of Teaching and Learning, 2021)
Mathematics is a subject that must be given since children are at the elementary school level up to college. However, mathematics is not much in demand by students, and mathematics is considered a difficult subject for the majority of students. This is reinforced by research conducted by TIMSS 2015 which illustrates that Indonesia is in the bottom 6th position, as well as the results of PISA 2018 which show rank 70 out of 78 countries. Some of the causes of this are the lack of variety and abstract mathematics learning, and this is contrary to the concrete way of thinking of elementary school students. The Indonesian Realistic Mathematics Learning Approach (PMRI) is an approach that can lead students to think from concrete situations to mathematical concepts by developing practical, logical, critical, and honest thinking patterns. PMRI also makes students understand problems in everyday life. The research aims to find out how effective PMRI is on the mathematics learning outcomes of fourth-graders infractions at MIN Setia Bhakti Trawas. This type of research is quantitative research with a quasi-experimental method by taking the subject using a purposive sampling technique. Data collection techniques in this study use tests. The results of the study using the N-Gain score test showed that the average N-Gain score for the PMRI class was 52.92%, which was included in the quite effective category. Meanwhile, the average N-Gain score for the control class is 27.44%, including the criteria for being not effective.